PENGARUH PELATIHAN DAN MOTIVASI BERDAGANG TERHADAP KEBERHASILAN UMKM BINAAN DISPERINDAG KABUPATEN BANDUNG - Diva Rizky Wandani, Dadang Munandar (PT Wahana Global Education, 2025)
This study aims to examine the effect of training (X₁) and trading motivation (X₂) on business success (Y) among MSMEs fostered by the Department of Trade and Industry of Bandung Regency. The research applied a quantitative method with purposive sampling involving 60 respondents who had attended training programs in 2022–2023. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression with the assistance of SPSS. The results indicate that both training and trading motivation have a positive and significant effect, either partially or simultaneously, on MSME business success. The R Square value shows that these variables explain a portion of business success, while other factors outside the study also contribute. Therefore, MSME success can be enhanced through relevant training and consistent trading motivation.